2016
DOI: 10.3390/catal6090128
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalysis: Fundamentals and Comparisons to Metal and Enzyme Catalysis

Abstract: Catalysis fulfills the promise that high-yielding chemical transformations will require little energy and produce no toxic waste. This message is carried by the study of the evolution of molecular catalysis of some of the most important reactions in organic chemistry. After reviewing the conceptual underpinnings of catalysis, we discuss the applications of different catalysts according to the mechanism of the reactions that they catalyze, including acyl group transfers, nucleophilic additions and substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 418 publications
(496 reference statements)
0
18
0
Order By: Relevance
“…Cinchona derivatives, Figure , are extensively employed as robust stereoselective catalysts and in addition were subject to many computational and experimental studies. These are flexible compounds that in solution exist as a mixture of conformers. Their function is directly related to their structure and their activity may be controlled via their conformational dynamics, this resembles enzymes function. , One way for the solvent to affect the reaction is by formation of a molecular complex with the catalyst, which may “select” one of the possible conformers of the asymmetric catalyst. If this conformer produces the largest ee, the solvent enhances or even determines the enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cinchona derivatives, Figure , are extensively employed as robust stereoselective catalysts and in addition were subject to many computational and experimental studies. These are flexible compounds that in solution exist as a mixture of conformers. Their function is directly related to their structure and their activity may be controlled via their conformational dynamics, this resembles enzymes function. , One way for the solvent to affect the reaction is by formation of a molecular complex with the catalyst, which may “select” one of the possible conformers of the asymmetric catalyst. If this conformer produces the largest ee, the solvent enhances or even determines the enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bond catalysis has been utilized as a powerful strategy in organic synthesis, particularly in enantioselective organocatalysis. Asymmetric catalysis by chiral hydrogen bond donors and the metal-free organocatalysis involving hydrogen bonding interactions benefit from formation of hydrogen bonds with substrates and clearly select the transition states that make stronger hydrogen bonds. Hydrogen bonds are also involved in the reaction mechanisms in the enzyme-catalyzed chemistry. , Substitution of cinchona by a good hydrogen bond donor like the thiourea group (which by itself is also a well-known organic catalyst that includes asymmetric derivatives) at the 6′ position, plays an important role in the catalytic functionality of the cinchona molecule. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 The esterication of alcohols with carboxylic acids in acidic chloroaluminate IL was investigated by Deng et al 19 Moreover, the esterication of alcohols with acid anhydrides in the presence of basic or acidic catalysts, such as 4-pyrrolidinopyridine and H 2 SO 4 , has been previously reported. 20,21 Lee et al 22 employed the metallic Lewis acids, such as Cu(OTf) 2 , Sc(OTf) 3 , Yb(OTf) 3 , and In(OTf) 3 , as catalysts in ILs to catalyze the ester-ication of alcohols with acetic anhydride. However, these catalysts suffer from some limitations such as long reaction time, low conversion rate, and lower yield.…”
Section: Introductionmentioning
confidence: 99%
“…53 Though the term organocatalysis was introduced by Ostwald in 1900, 54 it remained relatively forgotten until the 1970's when Hajos and Parrish (Hoffmann-La Roche), 55 and Eder et al (Schering) 55 independently reported the intramolecular aldol reaction catalyzed by (S)-proline, whose product was obtained in 99% yield and 93% enantiomeric excess. This asymmetric approach experienced a rebirth since 2000, when List et al 56 published their seminal work describing the employment of proline as organocatalyst in the enantioselective intermolecular aldol reaction between acetone and different aldehydes.…”
Section: Synopsis Of the Development Of Organocatalysts And Their Appmentioning
confidence: 99%